Psychological Well-Being dalam perspektif psikologi islam: Integrasi konsep kebahagiaan dan kesejahteraan psikologis - Zulfa, Intan Nala (Maliki Interdisciplinary Journal, 2026)
Mental health is an important aspect of human life that is influenced by various psychological, social, and spiritual factors. One factor that plays an important role in maintaining an individual’s psychological well-being is religiosity. This paper aims to examine the relationship between religiosity and mental health through the integration of psychological and Islamic perspectives. The method used in writing this paper is a literature review by examining various theories, empirical studies, and experts’ views on religiosity and mental health. The results of the study show that religiosity has a positive contribution to an individual’s mental health through several psychological mechanisms, such as meaning-making, coping strategies for stress, social support from religious communities, and the ability to regulate oneself through spiritual practices. In the Islamic perspective, values such as tawakal (trust in God), sabar (patience), syukur (gratitude), and ikhlas (sincerity) play an important role in helping individuals manage their emotions and face various challenges in life. The integration of psychological approaches and Islamic spiritual values provides a more holistic understanding of human mental health. Therefore, religiosity can be a protective factor that supports psychological well-being and helps individuals achieve balance between the spiritual, psychological, and social aspects of their lives.